TAMAN TEMATIK EDUKASI 5R SEBAGAI STRATEGI PEMANFAATAN LIMBAH SAMPAH ORGANIK DAN ANORGANIK - Tjokorda Istri Praganingrum; Ida Bagus Suryatmaja; I Gusti Agung Gede Eka Martiningsih (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Massive urban development and space utilization will ultimately trigger environmental problems. Issues related to the matter, such as reduced amount of green areas with less-controlled waste management, are important things need to be considered. In order to manage the problem, it is important to find a solution to arise hygiene behavior, as well as preserving green areas.  Providing education for community, starting from early ages, is considered to be a valuable effort. Education can be provided by making a thematic park with 5R (Reuse, Reduce, Recycle, Replace and Replant) principle, which can provide understanding through technology transfer model (TT) method, applying appropriate technology. In the future, the availability of thematic park will serve a novel medium for education training and community.